Quercetin and polycystic ovary syndrome, current evidence and future directions: a systematic review - Pourteymour Fard Tabrizi, Fatemeh; Hajizadeh-Sharafabad, Fatemeh; Vaezi, Maryam; Jafari-Vayghan, Hamed; Alizadeh, Mohammad; Maleki, Vahid (Journal of ovarian research, 2020)
Polycystic ovary syndrome (PCOS) is a polygenic endocrine disorder and the most common gynecological endocrinopathy among reproductive-aged women. Current remedies are often used only to control its signs and symptoms, while they are not thoroughly able to prevent complications. Quercetin is an herbal bioactive flavonoid commonly used for the treatment of metabolic and inflammatory disorders. Thus, this systematic review was conducted to evaluate the efficacy of quercetin supplementation in subjects with PCOS. Databases until March 2019 were searched. All human clinical trials and animal models evaluating the effects of quercetin on PCOS women were included. Out of 253 articles identified in our search, 8 eligible articles (5 animal studies and 3 clinical trials) were reviewed. The majority of studies supported the beneficial effects of quercetin on the ovarian histomorphology, folliculogenesis, and luteinisation processes. The effects of quercetin on reducing the levels of testosterone, luteinizing hormone (LH), and insulin resistance were also reported. Although quercetin improved dyslipidemia, no significant effect was reported for weight loss. It is suggested that the benefits of quercetin may be more closely related to antioxidant and anti-inflammatory features of quercetin rather than weight-reducing effects. Therefore, this review article provides evidence that quercetin could be considered as a potential agent to attenuate PCOS complications. However, due to the paucity of high-quality clinical trials, further studies are needed.